RISK CLASSIFICATION OF ROAD TRANSPORT OF DANGEROUS GOODS WITH METHOD FTA (Perner's Contacts, 2011)
The paper deals with the questions of road transport of dangerous goods and the text is adverted to the risks sequent to this specific transport. The safety of road transport of dangerous goods is influenced not only by characteristics of the utilized vehicle and by personality characteristics and knowledge of a driver, but also by the selected transport route. The next factor is accessibility of individual segments of road network for vehicles transporting dangerous goods or for a given category (weight) of vehicles. This problem is unequivocally solved by relevant rules, eventually by the road signalling. An integral part of roads safety is also psychology of behaviour of drivers by driving of vehicles transporting dangerous goods.
Keywords: dangerous goods; risk; road transport